2001
DOI: 10.1073/pnas.251534698
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of TNF-producing T cells in the bone marrow: A key mechanism by which estrogen deficiency induces bone loss in vivo

Abstract: In vivo studies have shown T cells to be central to the mechanism by which estrogen deficiency induces bone loss, but the mechanism involved remains, in part, undefined. In vitro, T cells from ovariectomized mice produce increased amounts of tumor necrosis factor (TNF), which augments receptor activator of NF-B ligand (RANKL)-induced osteoclastogenesis. However, both the mechanism and the relevance of this phenomenon in vivo remain to be established. In this study, we found that ovariectomy increased the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
439
6
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 471 publications
(465 citation statements)
references
References 47 publications
14
439
6
6
Order By: Relevance
“…We have shown that ovx increases T cell production of TNF through an expansion of the pool of TNF-producing T cells in the BM (11). T cell-produced TNF, in turn, augments RANKLinduced osteoclastogenesis (7,11).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We have shown that ovx increases T cell production of TNF through an expansion of the pool of TNF-producing T cells in the BM (11). T cell-produced TNF, in turn, augments RANKLinduced osteoclastogenesis (7,11).…”
Section: Discussionmentioning
confidence: 91%
“…Flow cytometry was performed as described (11), by using whole spleen or BM cells labeled with anti-CD3-conjugated phycoerythrin (PE) and either anti-CD25-conjugated FITC or anti-CD69-conjugated FITC antibodies (Pharmingen). Nonspecific staining was assessed by using FITC or PE-conjugated isotype-matched normal IgG antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TNFo-enhanced survival of osteoclasts appears to be associated with a reduction in apoptosis and the suppression of caspase activation (Lee et al, 2001). Knockout mice deficient in TNF-a and also TNFRl have a reduction in bone loss post-ovariectomy (in which estrogen-mediated resorption suppression is stopped) (Roggia et al, 2001). Another study has demonstrated that nude mice (lacking T lymphocytes) have the same protection from bone loss (Cenci et al, 2000).…”
Section: Discussionmentioning
confidence: 99%